FISCAL SUSTAINABILITY AND NATIONAL CURRENCY STABILITY: AN ANALYSIS THROUGH THE LENS OF TAX INCENTIVE EFFICIENCY (E Global Congress, 2026)
This research examines the critical nexus between fiscal sustainability and the stability of the national currency, specifically focusing on the efficiency of tax incentives. While tax incentives are often deployed as strategic tools to attract investment and stimulate growth, their mismanagement can lead to "fiscal erosion," widening budget deficits and destabilizing the exchange rate. By applying the "Fiscal-Monetary Nexus" framework, this study argues that inefficient tax expenditures fuel inflationary expectations and weaken the domestic currency. The paper provides a comparative analysis of incentive types and concludes with policy recommendations for aligning fiscal instruments with monetary stability goals.